A neotype for Hyla x-signata Spix, 1824 (Amphibia, Anura, Hylidae) - de Araujo Vieira, Katyuscia (2020)
The uncertain identity of Hyla x-signata Spix, 1824 has been a pervasive problem in the taxonomy of the genus Scinax. A species supposedly distributed from northeastern Brazil northwards to Colombia and Venezuela, described in a few lines without much information and with an accompanying figure, and its type specimen lost during World War II, combined to produce a curious situation. Twenty-one of the 39 species of the S. ruber Clade described in the last 50 years were considered to require a diagnosis from S. x-signatus by their authors. In most cases these had no other alternative than to gather information about this species from indirect sources, frequently pointing out the problems associated with its uncertain identity. In this paper, we review the taxonomic history of Hyla x-signata, designate a neotype, provide a redescription including advertisement call and sequence data, and diagnose it from all other species of the S. ruber Clade.